miR-29a Modulates GSK3β/SIRT1-Linked Mitochondrial Proteostatic Stress to Ameliorate Mouse Non-Alcoholic Steatohepatitis - Ya-Ling Yang (International Journal of Molecular Sciences, 2020)
MicroRNA-29a (miR-29a) has been shown to ameliorate hepatocellular damage, such as in the context of non-alcoholic fatty liver disease (NAFLD), steatohepatitis (NASH), and cholestatic injury. However, the mechanism mediating the hepatoprotective effect of miR-29a in diet-induced NASH remains elusive. In the present study, C57BL/6 mice of wild-type (WT) or miR-29a overexpression were fed with methionine–choline sufficient (MCS) or methionine–choline-deficient (MCD) diet for four weeks. The C57BL/6 mice harboring miR-29a overexpression presented reduced plasma AST, hepatic CD36, steatosis, and fibrosis induced by MCD. The TargetScan Release7.2-based bioinformatic analysis, KEGG pathway analysis, and luciferase reporter assay confirmed that miR-29a targets 3′UTR of glycogen synthase kinase 3 beta (Gsk3b) mRNA in the HepG2 hepatocyte cell line. Furthermore, miR-29a overexpression in the MCD-fed group resulted in inhibition of Gsk3b mRNA and GSK3β protein levels in the liver. GSK3β was notably expressed jointly with the extent of aggregated protein, which was then identified to be associated with mitochondrial unfolded protein response (UPRmt), but not with endoplasmic reticulum UPR (UPRER). Additionally, in silico analysis of protein–protein interaction, in vivo, and in vitro correlation analyses of protein expression demonstrated that GSK3β closely associated with sirtuin 1(SIRT1). Finally, the implication of SIRT1-mediated mitochondrial biogenesis in the perturbation of proteostasis was observed. We herein provide novel insight into a hepatoprotective pathway, whereby miR-29a inhibits GSK3β to repress SIRT1-mediated mitochondrial biogenesis, leading to alleviation of mitochondrial proteostatic stress and UPRmt in the context of NASH. miR-29a, GSK3β, and SIRT1 could thus serve as possible therapeutic targets to improve the treatment of NAFLD/NASH.